The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/bcr-2018-225009
|View full text |Cite
|
Sign up to set email alerts
|

Pyopericardium progressing to tamponade in a patient with immune thrombocytopenia

Abstract: Pericardial effusion can develop during any stage of pericarditis, and small effusions that appear rapidly can cause cardiac tamponade. Pyopericardium is a rare aetiology for tamponade. This is a case of an elderly diabetic lady, on steroid therapy for immune thrombocytopenia, who presented with fever and acute dyspnoea. She developed cardiac tamponade due to pyopericardium with as the causative organism. pyopericardium, in the absence of a primary focus of infection, progressing to tamponade is an uncommon sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Pyopericardium, or purulent pericarditis, is rare and rapidly fatal if left untreated. In treated patients, it has a mortality rate of up to 40%, related to cardiac tamponade and constriction 8–11 13–17. Pyopericardium can be caused by contiguous dissemination from pneumonia or empyema, by haematogenous spread, during cardiac or thoracic surgery or trauma 11 13 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyopericardium, or purulent pericarditis, is rare and rapidly fatal if left untreated. In treated patients, it has a mortality rate of up to 40%, related to cardiac tamponade and constriction 8–11 13–17. Pyopericardium can be caused by contiguous dissemination from pneumonia or empyema, by haematogenous spread, during cardiac or thoracic surgery or trauma 11 13 14.…”
Section: Discussionmentioning
confidence: 99%
“…Initial laboratory tests demonstrated haemoglobin of 106 g/L,8–12 white cell count 41.1×10ˆ9/L (4–10), with 38.8×10ˆ9/L neutrophils (16.4–32.8), platelets 395×10ˆ9/L (150–400), international normalised ratio 1.7, alanine aminotransferase 64 IU/L (<40) and lactate dehydrogenase 449 U/L (135–225). Cardiac enzymes remained normal.…”
Section: Case Presentationmentioning
confidence: 99%
“…Thrombocytopenia associated with pericarditis is described in a very small number of reports. 9,10 However, aside from the well-known role of platelets in hemostasis, lately they have been linked to inflammation as well. For instance, studies have shown that platelets promote inflammatory response in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) or magnetic resonant imaging (MRI) may aid the diagnosis as they can simultaneously show anatomical abnormalities of lung and mediastinal structures with better soft-tissue contrast and larger field of vision than a 2D-Echo. [ 1 9 10 ] Literature review demonstrated that Hemophilus influenza, Staphylococcus aureus , Viridans streptococci, Streptococcus pneumoniae and anaerobic bacteria to be the most common causative agent. However, few reports showed that gram-negative bacteria and fungi to be more frequent in immunocompromised hosts while others showed gram-positive coccis as the most commonly isolated organisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, few reports showed that gram-negative bacteria and fungi to be more frequent in immunocompromised hosts while others showed gram-positive coccis as the most commonly isolated organisms. [ 3 4 9 10 ] This pus filled pericardial space increases the intrapericardial pressure causing the compression of all cardiac chambers thereby limiting cardiac inflow leading to a marked fall in cardiac output and resulting in a cardiac tamponade. Hence early pericardiocentesis, initiation of early antibiotics therapy, 2D Echo guided placement of pericardium catheter reduces complications such as pneumothorax and cardiac or coronary laceration in these patients.…”
Section: Discussionmentioning
confidence: 99%